2001
DOI: 10.4049/jimmunol.166.6.3749
|View full text |Cite
|
Sign up to set email alerts
|

NK T Cell-Induced Protection Against Diabetes in Vα14-Jα281 Transgenic Nonobese Diabetic Mice Is Associated with a Th2 Shift Circumscribed Regionally to the Islets and Functionally to Islet Autoantigen

Abstract: The onset of autoimmune diabetes is related to defective immune regulation. Recent studies have shown that NK T cells are deficient in number and function in both diabetic patients and nonobese diabetic (NOD) mice. NK T cells, which are CD1d restricted, express a TCR with an invariant Vα14-Jα281 chain and rapidly produce large amounts of cytokines. Vα14-Jα281 transgenic NOD mice have increased numbers of NK T cells and are protected against diabetes onset. In this study we analyzed where and how NK T cells int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 44 publications
2
82
1
Order By: Relevance
“…In concordance, upregulation of CD1d expression restored the immunoregulatory function of NKT cells and prevented autoimmune diabetes [74]. Protection conferred by NKT cells was associated with a Th2 shift within the pancreatic islets, and IL-4 has been implicated as a key mediator of immunoregulation [69,75]. Stimulation of naïve T cells expressing a transgenic, diabetogenic TCR with their auto-antigen in the presence of NKT cells did not block the initial activation of the pathogenic T cells.…”
Section: Type 1 Diabetesmentioning
confidence: 57%
“…In concordance, upregulation of CD1d expression restored the immunoregulatory function of NKT cells and prevented autoimmune diabetes [74]. Protection conferred by NKT cells was associated with a Th2 shift within the pancreatic islets, and IL-4 has been implicated as a key mediator of immunoregulation [69,75]. Stimulation of naïve T cells expressing a transgenic, diabetogenic TCR with their auto-antigen in the presence of NKT cells did not block the initial activation of the pathogenic T cells.…”
Section: Type 1 Diabetesmentioning
confidence: 57%
“…A similar protection was observed after specific iNKT cell stimulation with exogenous ligands, a-galactosylceramide (a-GalCer) and its analogues [8][9][10][11]. Early reports suggested that iNKT cell protection was associated with the induction of a Th2 response to islet autoantigens [8,[10][11][12]. However, following studies using the transfer of anti-islet T cells showed that iNKT cells inhibit the differentiation of these auto-reactive T cells into effector cells during their priming in pancreatic lymph nodes (PLNs) [13,14].…”
Section: Introductionmentioning
confidence: 65%
“…The expansion of the NKT compartment due to Tg expression of the mouse inv. V␣14-J␣18 rearrangement has also been detected following the injection of the Tg construct directly into nonobese diabetic mice (39,40), indicating that the phenomenon is independent of the mouse's genetic background. Therefore, it is possible that differences in the timing of expression between the Tg human inv.…”
Section: Discussionmentioning
confidence: 96%